Molecular and Behavioral Differentiation among Brazilian Populations of Lutzomyia longipalpis (Diptera: Psychodidae: Phlebotominae) - Araki, Alejandra S.; Vigoder, Felipe M.; Bauzer, Luiz G. S. R.; Ferreira, Gabriel E. M.; Souza, Nataly A.; Araújo, Izeneide B.; Hamilton, James G. C.; Brazil, Reginaldo P.; Peixoto, Alexandre A. (PLOS Neglected Tropical Diseases, 2009)
Author Summary Lutzomyia longipalpis is the main vector of visceral leishmaniasis in the Americas. There is strong evidence that L. longipalpis is a species complex, but there is still no consensus regarding the number of species occurring in Brazil. We combined molecular and behavioral analyses of a number of L. longipalpis populations in order to help clarify this question. This approach has allowed us to identify two main groups of populations in Brazil. One group probably represents a single species distributed mainly throughout the coastal regions of North and Northeast Brazil and whose males produce the same type of copulation song and pheromone. The second group is more heterogeneous, probably represented by a number of incipient species with different levels of genetic divergence among the siblings that produce different combinations of copulation songs and pheromones. The high level of complexity observed raises important questions concerning the epidemiological consequences of this incipient speciation process.